OPCAB versus early mortality and morbidity: an issue between clinical relevance and statistical significance - Sergeant, Paul; Wouters, Patrick; Meyns, Bart; Bert, Christophe; Van Hemelrijck, Jan; Bogaerts, Chris; Sergeant, Gregory; Slabbaert, Koen (European journal of cardio-thoracic surgery, 2004)
To evaluate the impact of OPCAB on major postoperative events in a large consecutive cohort of patients, covering the complete spectrum of risk. A consecutive series of 3333 CABG patients operated in a single institution (Jan/97-Jan/03) is analyzed after a complete (98%) midterm reengineering towards off-pump surgery (Oct/99). Patients in cardiogenic shock are excluded. The on- (N=1593) or off-pump (N=1740) datasets are comparable for most demographic and non-cardiac variability. The studied events are early mortality, early stroke, early infarct, early dialysis and hospital stay. Three methods adjust for possible patient selection: similar datasets, forced inclusion of a saturated OPCAB propensity score and finally multivariate correction. Non-risk adjusted. The 3-month survival was 96.7+/-0.4% (OPCAB) and 95.9+/-0.5% (ECC) (P=0.2). The 8-day freedom from stroke was 99.4+/-0.2% (OPCAB) and 98.5+/-0.3% (ECC) (P=0.004). The prevalence of dialysis was 1.67% in OPCAB and 2.27% in ECC (P=0.2). The 8-day freedom from infarct was 98.4+/-0.2% (OPCAB) and 98.3+/-0.2% (ECC) (P=0.7). The freedom from hospital discharge day 15 was 17.6+/-0.9% (OPCAB) and 18.4+/-0.8% (ECC) (P=0.001). Propensity score corrected and adjusted for event-related variability. The survival effect remained non-significant (P=0.3), also for patients with a EuroSCORE>8 (P=0.9). The stroke effect became non-significant (P=0.2), but stayed significant for patients with severe internal carotid artery stenosis (P=0.02). The dialysis-effect remained non-significant (P=0.6), also for patients with an elevated creatinine (P=0.7). The early infarct-effect remained non-significant (P=0.8), also for the female patients (P=0.8). The hospital discharge was significantly influenced by the OPCAB approach for the total group (P=0.02) as well as for the patients with EuroSCORE>8 (P=0.01). The observed 20% reduction of mortality, 60% reduction of stroke and 20% reduction of dialysis were partly neutralized by the adjusting methods and demand, at least, larger datasets to obtain statistical significance. Subdatasets with fewer patients but higher risk identified risk-reducing effects for stroke. Hospital stay was shortened by the OPCAB approach. The interactions between risk, number of patients and the risk-reducing effect are the cornerstones of evidence generation for the OPCAB approach. These results were obtained through a very strict reengineering and cannot be extended to all OPCAB programs.